Structural Elucidation of A Bioactive Compound from the Leaves of Neptunia prostrate - Paul, S.B.; Nath Choudhury, Swarnali; De, Biplab (Asian Journal of Chemistry, 2011)
The analgesic activity of the methanolic extract of leaves of Neptunia prostrate and its separated fractions were studied in acetic acid induced model. The in vivo antiinflammatory was also studied using Carageenan induced rat paw edema. The result of both the studies indicated that the extract and its components possessed significant analgesic activity as well as antiinflammatory activity at the dose 100 mg/Kg. Both the activities were compared with standard drug aspirin for analgesic and diclofenance sodium for antiinflammatory. The structure of the bioactive compound has been characterized on the basis of spectral data such as IR, 1H NMR, 13C NMR and mass spectral studies.